Journavx (Suzetrigine): A Safer Alternative for Pain Relief? - Saqib Ali; Muhammad Affan Ilyas (Journal of the Pakistan Medical Association, 2025)
Madam, Opioids are widely used to manage moderate to severe acute pain especially post-surgical acute pain; however, these analgesics have several limitations, including the development of tolerance, addiction, physical dependence, constipation, respiratory depression, and various behavioural side effects that frequently lead to patients’ non-compliance. Older adults, due to age-related physiological changes and reduced metabolic capacity, experience higher rates of chronic pain from both cancerous and non-cancerous conditions and are more susceptible to adverse opioid reactions1. The widespread use of opioids has contributed to a growing public health crisis, with opioid overdose deaths in the United States rising almost every year since the late 1990s. This increase has been particularly dramatic since 2019, with opioid-related deaths surging by 64% between 2019 and 2022, reaching 81,806 deaths (25.0 per 100,000) in 2022. Overall, opioid-related mortality has increased tenfold, highlighting the urgent need for alternative pain management strategies2. The U.S Food and Drug Administration (FDA) for the first time approved the first of its kind non-opioid analgesic, Journavx (Suzetrigine), for moderate to severe acute pain in adults. Journavx is a potent allosteric inhibitor of voltage-gated sodium channels 1.8 (Nav1.8) that are expressed by peripheral neurons and not by the neurons of the central nervous system. Therefore, it does not cause dependence and tolerance like opioids. FDA recommends twice-daily Journavx for the treatment of adults with moderate-to-severe acute pain3.The approval comes after two randomised double-blind placebo and active controlled trials of acute surgical pain, one following abdominoplasty and the other following bunionectomy. Suzetrigine proved to be highly efficacious in reducing pain as compared toplacebo in both the trials4. The drug is to be taken orally. The most common adverse effects reported in the trial were itching, muscle spasms, rash and increased levels of creatine phosphokinase. Additionally, since the drug is metabolised by cytochrome P450 3A, it should be avoided with other drugs, and foods and drinks that inhibit the enzyme. The safety of the drug has not yet been evaluated in pregnant women and children5. Further research is necessary to evaluate its efficacy and safety in children and pregnant women, as well as its potential role in treating diabetic neuropathy should be thoroughly studied3. To maximise its public health benefits, pharmaceutical companies should focus on improving its affordability and accessibility. Urgent action is necessary, including expanding clinical trials to various populations, accelerating regulatory approvals, and strengthening collaborations between governments and healthcare organisations to facilitate widespread distribution.